MAINTAINING IDENTITY IN THE FLOW OF GLOBALIZATION - Yogi Prayudi; Jaja Jaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Language use in public spaces not only reflects aspects of communication but also represents national identity, symbolic power, and the direction of state policy. In Indonesia, regulations on the use of Indonesian have been regulated through various legal instruments, such as Law Number 24 of 2009 and Presidential Regulation Number 63 of 2019. However, implementation in the field still faces challenges, such as the dominance of foreign languages, weak law enforcement, and low social awareness. On the other hand, the preservation of regional languages through the practice of bilingual signage is a form of harmony between national and local languages. This article highlights the importance of language policies that are not only normative, but also strategic and inclusive, by proposing four main recommendations: language literacy campaigns, creative language design, proportional regulatory enforcement, and multi-sectoral collaboration. With a comprehensive approach, public spaces can become a vehicle for dignified representation of Indonesian while respecting national linguistic diversity.